2003
DOI: 10.1007/978-1-4757-3714-1
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Hyperstructure Theory

Abstract: Softcover reprint of the hardcover 1st edition 2003No part of this work may be reproduced, stored in a retrieval system, or transmitted in any form or by any means, electronic, mechanical, photocopying, microfilming, recording or otherwise, without written permission from the Publisher, with the exception of any material supplied specifically for the purpose of being entered and executed on a computer system, for exclusive use by the purchaser of the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
421
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(428 citation statements)
references
References 0 publications
0
421
0
7
Order By: Relevance
“…Later on, people have observed that hyperstructures have many applications to several branches of both pure and applied sciences (see [2][3][4][5]). In particular, a semihypergroup is the simplest algebraic hyperstructure which possess the properties of closure and associativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, people have observed that hyperstructures have many applications to several branches of both pure and applied sciences (see [2][3][4][5]). In particular, a semihypergroup is the simplest algebraic hyperstructure which possess the properties of closure and associativity.…”
Section: Introductionmentioning
confidence: 99%
“…In [23], Heidari and Davvaz applied the theory of hyperstructures to ordered semigroups and introduced the concept of ordered semihypergroups, which is a generalization of the concept of ordered semigroups. Also see [2]. The work on ordered semihypergroup theory can be found in [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The hyperstructure theory and its applications have been investigated by the contribution of many mathematicians. The principal notions of hyperstructure theory can be found in [9,10,11,12,14,29].…”
Section: Introductionmentioning
confidence: 99%
“…In a classical algebraic structure, the composition of two elements is an element, while in an algebraic hyperstructure, the composition of two elements is a set. Since then, hundreds of papers and several books have been written on this topic, see [2][3][4].…”
Section: Introductionmentioning
confidence: 99%